Efficacy of Neoadjuvant Chemotherapy with Capecitabine plus Oxaliplatin in the Treatment of Locally Advanced Sigmoid Colon Cancer Invading the Urinary Bladder: A Report of Three Cases - Tsutomu Takenami; Shingo Tsujinaka; Jun Takahashi; Sawako Tamaki; Ryo Maemoto; Rintaro Fukuda; Hideki Ishikawa; Nao Kakizawa; Fumi Hasegawa; Rina Kikugawa; Yasuyuki Miyakura; Koichi Suzuki; et al. (Case Reports in Surgery)
Introduction. We herein present three cases of locally advanced colon cancer (LACC) invading the urinary bladder, in whom combined neoadjuvant chemotherapy with surgical intervention was effective in disease control and preserving urinary function. Case Presentation. Before neoadjuvant chemotherapy, all three cases underwent loop transverse colostomy for symptomatic colonic obstruction. Case 1: after 6 courses of capecitabine plus oxaliplatin (CAPOX), we performed sigmoid colectomy and partial resection of the bladder. The histological examination revealed pathological complete response (pCR). The final diagnosis was ypStage 0 (ypT0ypN0M0). Case 2: after 13 courses of CAPOX plus bevacizumab, we performed Hartmann’s operation with partial resection of the bladder. The histological examination revealed pCR. The final diagnosis was ypStage 0 (ypT0ypN0M0). Case 3: after 6 courses of chemotherapy with CAPOX plus bevacizumab, we performed sigmoid colectomy and partial resection of the bladder. The pathological response was grade 1a according to the Japanese Classification of Colorectal Carcinoma. The final diagnosis was ypStage IIC (ypT4bypN0M0). All three cases underwent capecitabine-based adjuvant chemotherapy after radical surgery and patients are alive without recurrence. Conclusion. Neoadjuvant chemotherapy with CAPOX with or without bevacizumab followed by radical surgery could be an effective treatment option for LACC invading the urinary bladder.